2013
DOI: 10.1016/j.aap.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Teen driving in rural North Dakota: A qualitative look at parental perceptions

Abstract: Motor vehicle crashes are the leading cause of death among teens in the United States. Graduated driver licensing (GDL) programs allow new drivers to gain driving experience while protecting them from high-risk situations. North Dakota was one of the last states to implement GDL, and the current program does not meet all of the best practice recommendations. This study used qualitative techniques to explore parents' perceptions of the role teen driving plays in the daily lives of rural North Dakota families, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…However, we found that parents were more likely to worry “a lot” about their teen drivers and place more restrictions on them during the learner permit phase, during which the teen is required to have an adult supervisor in the vehicle, than when teens are newly licensed and able to drive independently under certain conditions. This finding is consistent with results of previous studies indicating that many parents lack awareness of the most high-risk situations for teen drivers (Gill, Shults, Cope, Cunningham, & Freelon, 2013). Because teens quickly develop basic vehicle handling skills, parents may mistakenly believe that their teen is ready to drive independently (Goodwin, Foss, Margolis, & Waller, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that parents were more likely to worry “a lot” about their teen drivers and place more restrictions on them during the learner permit phase, during which the teen is required to have an adult supervisor in the vehicle, than when teens are newly licensed and able to drive independently under certain conditions. This finding is consistent with results of previous studies indicating that many parents lack awareness of the most high-risk situations for teen drivers (Gill, Shults, Cope, Cunningham, & Freelon, 2013). Because teens quickly develop basic vehicle handling skills, parents may mistakenly believe that their teen is ready to drive independently (Goodwin, Foss, Margolis, & Waller, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, these five states had among the highest proportions of students who drove. Adolescents in these states are more likely to begin driving at younger ages than adolescents living in more densely populated states, and, because of the rural nature of the states, they may drive longer distances [27], thereby increasing the opportunity to engage in TWD.…”
Section: Discussionmentioning
confidence: 99%
“…Given that enforcement of GDL conditions and restrictions is undertaken by police with finite resources, the success of GDL not only requires voluntary compliance by young drivers themselves, but also requires parents to act as pseudo‐enforcers by encouraging and monitoring compliance where and when possible (see also Voas and Kelley‐Baker, ). Pleasingly, research consistently demonstrates that, in general, parents and young drivers are supportive of GDL (e.g., parents supportive of nighttime driving restrictions [Gill et al., ]; teens supportive of nighttime driving restrictions, mobile phone restrictions, and passenger limits [Williams, ]).…”
mentioning
confidence: 99%